Awareness of feeding patterns in first-time mothers - KAPOOR, Ms.PRIYA; DHARMADHIKARI, Ms. GAYATRI; SALUNKE, Ms. VAISHNAVI (Indian Journal of Child Health, 2022)
Background: Feeding is a vital source of energy and a necessity for survival. It is pivotal that mothers of new-born are aware of correct feeding patterns as it may impact the feed and health of the infant. The present study aimed to explore the awareness of various breastfeeding and bottle-feeding patterns in first-time mothers of infants up to 6 months of age. Materials and Methods: The participants in the study were 56 first-time mothers with infants <6-month old who had no medical history. The study design was exploratory and duration of study was 3 months. A questionnaire was used in the study to elicit information about feeding pattern awareness. The questionnaire consisted of eight Marathi-language questions based on eight feeding variables. Data were not normally distributed hence non-parametric test, Chi-square analysis was used for statistical analysis. Results: Results revealed in both the groups, the cradle position was employed for feeding. In certain mother-infant pairings, the mouth of the newborn was found to be well latched to the breast. In both groups, there was a lot of parent-child interaction when feeding. In general, 100% of infants acquire weight gradually. Conclusion: Overall, mothers in both the groups had a strong understanding of breastfeeding and bottle-feeding, which is very empirical for safe and efficient feeding.